Assessing the structure and functioning of the southern North Sea ecosystem with a food-web model. (1st November 2018) - Stäbler, Moritz; Kempf, Alexander; Temming, Axel
Abstract: Single species stock assessment models are, and will remain, the workhorse of fisheries management. However, they are incapable of assessing the structure and functioning of the ecosystem the fisheries operate in. This study describes the trophic structure of the southern North Sea and the flows between the nodes of its food-web. It is based on the outputs of an Ecopath food-web model of the North Sea south of the Skagerrak (ICES area VIb and c), parametrized representing the year 1991. The study also compares the southern to a whole North Sea Ecopath model (whole ICES area IV) parametrized for the same year, 1991. The two dominant flows of biomass led from primary producers to detritus, and from there into benthos. The southern North Sea differed from the whole North Sea representation in its fish community composition, primarily attributable to the biogeography of the species. Flatfish were caught more and roundfish less in the south, even with a nominally identically gear, to wit, otter trawlers. The largely different fish and catch compositions call for a specific, local management of the shallow southern North Sea's fisheries, which is based on ecosystem boundaries, rather than politically defined areas. Beyond fished stocks, food-web network indicators suggest that both systems functioned similarly, if compared to a global set of Ecopath models. They also deem the 1991 North Sea and its southern sub-part a densely woven, mature and resilient food-web. Highlights: We holistically assess the 1991 southern North Sea with an Ecopath food-web model. Its different compartments are highly interlinked and the food-web is densely woven. Ecological theory hence suggests high resilience of the ecosystem. Fish community and catch composition differ from the North Sea as a whole. Despite that, southern and total North Sea structure and function very similarly.